Validation of Indonesian Words Memory Test - Erydani Anggawijayanto; Thomas Dicky Hastjarjo (Universitas Ahmad Dahlan, 2021)
Working memory not only temporarily stores information but also actively processes information to perform complex cognitive tasks. Working memory components have different functions such as storing specific verbal and auditive information, visual and spatial information storage areas and there are components that control both systems. One way to retrieve stored information is by recall technique. This study used twelve concrete nouns tested in the form of 12 sequence formats. The twelve formats were tested on 120 people so that each format was tested on 10 participants. Each word produces scores based on achievement tests in each sequence. The participants of this study were adult individuals aged 19-30 years, consisting of 24 male and 96 female participants. Difficulty level (p) of each word, i.e the number of correct answers is divided by the number of total answerers, calculated in each order format. For each sequence a word is chosen with the difficulty level of p = 0.03-0.05. The participants of this study were adult individuals aged 19-30 years, consisting of 24 male and 96 female participants. This study developed a memory test of Indonesian nouns that had psychometric parameters.